Ocorrência, distribuição e atividade de cães (Canis lupus familiaris) na ARIE Mata de Santa Genebra (Campinas – SP), o seu impacto para a mastofauna nativa e propostas para controle. - Feliciano, Renato D’Elia (Universidade Federal de São Carlos, 2021)
The introduction of exotic species is an increasingly recurrent event in a context of expanding human occupation, destruction and fragmentation of habitats, alteration of natural ecosystems and globalization, with the impact of these introductions being considered the second largest cause of species extinction. In this sense, the domestic dog (Canis lupus familiaris) appears as an important character, considering that it is a cosmopolitan species, with great adaptive plasticity, generalist habits, introduced in most parts of the world and with several records of attacks and predation on native fauna in different continents. Thus, to deeply understand the dynamics of these dogs occurrences in natural areas, such as Conservation Units, from the evaluation of the places, periods and seasons of greatest activity is of crucial importance in order to understand this presence and its possible impacts on native fauna. In this study, we aimed to conduct an updated survey of the presence of domestic dogs within the Area of Relevant Ecological Interest (ARIE) Mata de Santa Genebra, focusing on the number of individuals, the areas of major activity and the interactions with non-flying native mammals species in the area. The sampling was done by collecting images with camera traps and field observation at twelve different points in the area, resulting in a sampling effort of 2754 camera-days. From 40-second filming, 316 mammal records were obtained which 88 of them documented the presence of dogs in the area. The analysis of the records allowed the identification of ten native mammals (Didelphis albiventris, Didelphis aurita, Sapajus nigritus, Dasypus novemcinctus, Cerdocyon thous, Procyon cancrivorus, Puma concolor, Leopardus pardalis, Silvivagus brasiliensis and Hydrochoerus hydrochaeris) and the Canis lupus familiaris (with 24 dogs distinct individuals identified). The data obtained were confronted with AIRE historical data recorded during the period from 2016 to 2020, in order to observe possible changes in the ...